CERRAHPAŞA TIP FAKÜLTESİ ÖĞRENCİLERİNİN TIP EĞİTİMİ ve MEZUNİYET SONRASI İLE İLGİLİ TUTUMLARI - KÖKSAL, Selçuk; VEHİD, Suphi; TUNÇKALE, Aydın; ERGİNÖZ, Ethem; KAYPMAZ, Ayşe; SİPAHİOĞLU, Fikret; ÇERÇEL, Ali; ÖZBAL, Ahmet Nejat (Cerrahpaşa Medical Journal, 2014)
Background and Design.-Health indicators are not reached desirable level in our country. A good organisation of primary health care service, which depends on the quantity and quality of general practitioners employed at primary health care units, can increase health indicators. Knowing that medical schools are the only source of education as a general practitioner, we tried to determine the purposes of enrolling in a medical school and attitudes of 1340 medical students to the post graduate situation from the second to the six class of the Cerrahpaşa Medical School. The data obtained from the students by the questionnaire forms were analysed by appropriate statistical methods. Results.-We determined that medical education was first preference of the 586 student, the second preference of the 127 student and the third preference of the 126 student. We determined that medical education was not first three preference on 40% of the students. A lot of students were filling regret for starting education in a medical school. Only 2.2% of the students were thinking to work as a general practitioner, 87% of them wanted to become specialised. Conclusion.-In order to have good health indicators we need good organisation of the primary health care service. The importance of primary health care service must be emphasised in medical curriculum. General practitioners who work at primary health care service must be supported morally and physically.